Sensory integration of danger and safety cues may explain the fear of a quiet coyote - Smith, Jennifer E.; Carminito, Chelsea; Hamilton, Shea; Newcomb, Kate Lee; Randt, Clare; Travenick, Sarah (Proceedings of the Royal Society. B, Biological sciences, 2023)
Sensory integration theory predicts natural selection should favour adaptive responses of animals to multiple forms of information, yet empirical tests of this prediction are rare, particularly in free-living mammals. Studying indirect predator cues offers a salient opportunity to inquire about multimodal risk assessment and its potentially interactive effects on prey responses. Here we exposed California ground squirrels from two study sites (that differ in human and domestic dog activity) to acoustic and/or olfactory predator cues to reveal divergent patterns of signal dominance. Olfactory information most strongly predicted space use within the testing arena. That is, individuals, especially those at the human-impacted site, avoided coyote urine, a danger cue that may communicate the proximity of a coyote. By contrast, subjects allocated less time to risk-sensitive behaviours when exposed to acoustic cues. Specifically, although individuals were consistent in their behavioural responses across trials, ‘quiet coyotes’ (urine without calls) significantly increased the behavioural reactivity of prey, likely because coyotes rarely vocalize when hunting. More broadly, our findings highlight the need to consider the evolution of integrated fear responses and contribute to an emerging understanding of how animals integrate multiple forms of information to trade off between danger and safety cues in a changing world.